THE ALGORITHM OF GIVING AUTOMATIC HARAKAT ON ARABIC SCRIPT - Dini Hidayatul Qudsi; Maksum Ro’is Adin Saf (Universitas Trunojoyo Madura, 2017)
The majority of Arabic reference books in Arabic writing without a vowel/harakat causestudents to have difficulty in learning Arabic. Reading Arabic Script without harakatrequires an understanding of the science of Nahwu-Sharf (Arabic Grammar) to be able tounderstand its contents. Therefore, in this study the basic rules of Nahwu-Sharf Sciencehave been translated into an algorithm that can be used to provide an automatic harakaton Arabic script (without harakat). Based on the interview results with the expert, sixexamples of sentences that represented the types(conditions) of basic sentences in theArabic language have been used as scenarios to examine the generated algorithm. Theallowed sentence is limited to one sentence only and cannot be in the form of poetry orsatire. Additionally, Cyclomatic Complexity Testing is used to examine scenarios in a testcase. All the steps of the Cyclomatic Complexity have been performed, which are creatingthe flowgraph, calculating the independent path, and testing scenario. The scenarios wereexamined in a test case through 13-path test case examination and result match withexpected output. In addition, 24 examples which represented the six conditions have beenutilized to examine for more detailed analysis and also results accuracy 100% inaccordance with the basic rules of Nahwu-Sharf science.